2015
DOI: 10.1051/epjconf/20158600017
|View full text |Cite
|
Sign up to set email alerts
|

Role of neutron rearrangement channels in sub-barrier fusion

Abstract: Abstract. Different factors influencing the sub-barrier fusion enhancement owing to neutron rearrangement with positive Q values are studied. It was found that opposite to the previous opinion the presence of positive Q values is necessary but not sufficient to observe enhancement of the sub-barrier fusion. "Rigidity" of colliding nuclei with respect to collective excitations plays a crucial role for the sub-barrier fusion enhancement due to neutron rearrangement. Neutron binding energy has a strong impact but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…[4], as indicated by the gray solid curve, as a function of the system parameter . In two previous studies [26,27], we demonstrated that fusion hindrance appears at the energy threshold = 87.29, 88.9, 67.5, 73.42, and 72.95 MeV for the 58 Ni+ 56 Fe, 64 Ni+ 64 Ni, 28 Si+ 100 Mo, 32 S+ 89 Y, and 34 S+ 89 Y systems, respectively. These values are presented in Fig.…”
Section: A the Fusion Cross Sectionmentioning
confidence: 56%
See 4 more Smart Citations
“…[4], as indicated by the gray solid curve, as a function of the system parameter . In two previous studies [26,27], we demonstrated that fusion hindrance appears at the energy threshold = 87.29, 88.9, 67.5, 73.42, and 72.95 MeV for the 58 Ni+ 56 Fe, 64 Ni+ 64 Ni, 28 Si+ 100 Mo, 32 S+ 89 Y, and 34 S+ 89 Y systems, respectively. These values are presented in Fig.…”
Section: A the Fusion Cross Sectionmentioning
confidence: 56%
“…77 model significantly underestimates the measurements of the fusion-evaporation excitation functions at sub-barrier energies for a number of systems. However, it appears that this potential model achieves better performance for the lighter colliding systems 12 C+ 30 Si, 28 Si+ 30 Si, and 24 Mg+ 30 Si. These results can be understood by observing the radial behavior of the Coulomb plus nuclear potentials used in the CC calculations (see the inset in the figure).…”
Section: A the Fusion Cross Sectionmentioning
confidence: 99%
See 3 more Smart Citations